(untitled) (Third Sector Social Economic Review, 2025)
This study aimed to examine digital consumer reviews for Komagene, Maydanoz Döner, and Popeyes across fourteen selected provinces representing Turkey’s seven geographical regions, using a sentiment analysis approach, in order to reveal regional differences in consumer satisfaction. Positive and negative reviews were systematically classified using MAXQDA and Excel, and regional consumer satisfaction was analyzed across multiple dimensions. The findings indicated that Komagene achieved higher positive review rates in the Central Anatolia and Marmara regions, while Maydanoz Döner demonstrated strong positive performance in the Black Sea and Eastern Anatolia regions, primarily driven by service quality and satisfaction-focused feedback. Popeyes, on the other hand, exhibited low positive and high negative review rates in most regions, with negative feedback largely associated with service issues and dissatisfaction. Regional analysis highlighted significant differences between brands and across regions, showing that positive feedback centered on satisfaction and service quality, versus negative feedback focused on service problems and dissatisfaction, played a key role in shaping the brands’ strategic positioning. The study is the first to conduct a comprehensive digital review analysis covering all geographical regions of Turkey for these three brands, providing insights for businesses to develop region-specific strategies and contributing a unique regional perspective to the literature.